TRADISI PENGHORMATAN PATUNG DAN IKONOGRAFI PARA KUDUS SEBAGAI SARANA BERIMAN UMAT KATOLIK DI INDONESIA - Andreas Mariano; Yohanes Alfrid Aliano (Aggiornamento, 2022)
The presence of statues and iconography of the saints has been present in ancient Israel as a means of worship and a place for storing sacred objects. His presence has also decorated the temple with beauty. Meanwhile, in the early days of the Church the presence of statues and iconography was a symbol of faith. In addition, the two sacred objects are used as a means to evangelize. These are some of the things that are the focus of this paper. The understanding of these two objects is often criticized from outside the Church. The difference in Tradition between the Eastern and Western Churches makes these sacred objects foreign to both. However, this understanding is important because the Tradition of the two Churches has one root, namely the Apostolic source. That is, many historical stories are found in this writing. This is in line with the sources used for the writing methodology, so as not to deviate from the discussion. Therefore, apologetics about sculpture and iconography provides an opportunity, so that there is no doubt. In the end, this writing takes part in the mystical spiritual formation of prayer to the saints through sculpture and iconography.